The Republic of Yemen : 2013 Article IV Consultation. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
This staff report on the Republic of Yemen's 2013 Article IV Consultation highlights economic development and policies. The macroeconomic situation stabilized in 2012, but the recovery remains fragile. After contracting by more than 12 percent in 2011, real GDP is estimated to have grown by 2.4 percent in 2012, reflecting an easing of supply bottlenecks, and utilization of part of idle capacity. On the other hand, oil production declined further, due to continued sabotage of the pipelines. Average inflation declined to 9.9 percent from 19.5 percent in 2011, reflecting the appreciation of the rial to its pre-crisis level, the moderation of international food prices, and the easing of supply shortages.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet